Pathogenic Fungi Causing Disease on Merbau Plants (Intsia spp.) in Sawesuma Village Forest, Urunum Guay District, Jayapura Regency - Cahyaningsih, Ayu; Tanjung, Rosye H.R.; Runtuboi, Dirk Y.P. (Jurusan Biologi FMIPA Universitas Cenderawasih, 2025)
Plant diseases result from the interaction of virulent pathogens, susceptible host plants, and favorable environmental conditions, often indicated by the appearance of growth abnormalities, referred to as symptoms, across various plant parts.This study aims to identify the species of Intsia plants affected by diseases and to determine the types of fungi responsible for causing diseases in Intsia sp. This research involved field surveys, observations, and sampling of pathogenic fungi, followed by fungal isolation and identification at the Mycology Laboratory and the FMIPA Biology Laboratory, Cenderawasih University, Jayapura. The methods employed included site surveys, sampling, isolation of pathogenic fungi causing diseases in Intsia sp. , identification of disease-causing fungi, and pathogenicity testing. Based on observations, the Intsia species affected by diseases were Intsia bijuga and Intsia palembanica. Four fungal species were identified as disease-causing agents in Intsia plants, including Aspergillus sp., Penicillium sp., Fusarium sp., and Mucor sp., along with one unidentified fungal species.